Shaping techniques of adsorbents and their applications in gas separation: a review. Issue 43 (26th September 2022) - Wu, Junye; Zhu, Xuancan; Yang, Fan; Wang, Ruzhu; Ge, Tianshu
Abstract : This paper reviews recent advances in the shaping adsorbents: alternative geometric forms, key metrics for evaluation, typical steps of main shaping techniques, etc., are discussed, which can serve as a reference for structured adsorbent design. Abstract : To facilitate the large-scale deployment of the adsorption-based gas separation technique, the integration of adsorbents derived from laboratories with gas–solid contactors in the industrial system should be considered. Compared to the conventional method to pack the adsorbent powder into the reaction bed, the strategies of shaping materials into structured adsorbents and utilizing gas–solid contactors with advanced architectures present improved efficiency and attract increasing attention. The reduced gas flow pressure drop and the increased thermal and mass transfer performance contribute to cutting down the operation energy consumption. To this end, this paper reviews the recent advances in the shaping process for adsorbents. First, the alternative geometric forms of structured adsorbents are introduced, and key metrics for structured adsorbent evaluation are summarized. Then, the effects of textural and geometric properties are discussed. Next, the typical steps and characteristics of the main techniques for adsorbent shaping are elaborated. The gas separation performance of structured adsorbents is compared. Further, from a practical point of view, the routes to integrate these structured adsorbents into suitable gas–solid contactors, as well as the corresponding cyclic processes and operation strategies, are discussed briefly. It is concluded that shaping techniques should be appropriately adopted according to the adsorbent properties, and the structure of the adsorbent should be designed according to the application requirements. This paper can serve as a reference for structured adsorbent design and promote the development of the adsorption-based gas separation technique.